OPTIMIZING VIRGIN COCONUT OIL YIELD AND QUALITY USING LACTIC ACID BACTERIA FROM BLONDO WITH CHILLING-THAWING METHOD - Chaidir, Riri Rimbun Anggih; Jariah, Ainun; Nevara, Gita Addelia; Murti, Tri; Rohayu, Andini Cindy (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Increasing demand for Virgin Coconut Oil (VCO) presents a promising opportunity to improve the economy in Indonesia. Various methods for VCO production have been explored to optimize yield and ensure desirable organoleptic and physicochemical qualities. Modifying the oil extraction process often necessitates costly equipment. In this study, VCO was extracted by combining the chilling-thawing method with the addition of lactic acid bacteria (LAB) isolated from blondo. The process began with the isolation and characterization of LAB isolates, followed by the application of the chilling-thawing method and addition of 2% LAB starter, then assessed for their consumer preference through a questionnaire. This innovative process yielded VCO at a rate of 35.78-46.65% using three LAB isolates (BAL 1-3) from blondo samples, representing an improvement over previous studies employing similar methodologies. Moreover, hedonic evaluation revealed a higher consumer preference for LAB-treated VCO compared to the control, further highlighting the effectiveness of LAB treatment in combination with the chilling-thawing method.